2020
DOI: 10.1002/aps3.11380
|View full text |Cite
|
Sign up to set email alerts
|

Digitally deconstructing leaves in 3D using X‐ray microcomputed tomography and machine learning

Abstract: X-ray microcomputed tomography (microCT) can be used to measure 3D leaf internal anatomy, providing a holistic view of tissue organization. Previously, the substantial time needed for segmenting multiple tissues limited this technique to small data sets, restricting its utility for phenotyping experiments and limiting our confidence in the inferences of these studies due to low replication numbers. METHODS AND RESULTS: We present a Python codebase for random forest machine learning segmentation and 3D leaf ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Images were reconstructed using TomoPy [ 54 ] for all ALS samples or using the in-house reconstruction platform for SLS or APS samples. Reconstructed scans were processed using published methods [ 32 , 55 ], and image stacks were cropped to remove tissue that was dehydrated, damaged or contained artefacts from the imaging or reconstruction steps. The final stacks contained approximately 500–2000 eight-bit grayscale images (downsampled from 16 or 32-bit images).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were reconstructed using TomoPy [ 54 ] for all ALS samples or using the in-house reconstruction platform for SLS or APS samples. Reconstructed scans were processed using published methods [ 32 , 55 ], and image stacks were cropped to remove tissue that was dehydrated, damaged or contained artefacts from the imaging or reconstruction steps. The final stacks contained approximately 500–2000 eight-bit grayscale images (downsampled from 16 or 32-bit images).…”
Section: Methodsmentioning
confidence: 99%
“…To extract surface area and volumes, mesophyll cells, airspace, vasculature (combined veins and bundle sheath) and background (including the epidermis) were segmented using published methods [ 32 , 55 ] and ImageJ [ 57 ]. Airspace volume ( V pores ), mesophyll cell volume ( V cells ), both summing up to the total mesophyll volume ( V mes ), vasculature volume ( V veins ) and the surface area exposed to the intercellular airspace (SA mes ) were then extracted using published methods [ 32 ] with the ImageJ plugin BoneJ [ 58 ], or using a custom Python program [ 55 ] ( ). SA mes / V mes is less sensitive to leaf thickness than the commonly measured S m , i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The segmentation of the gray values of microCT data sets is increasingly being automated by algorithms due to the advancing technical possibilities ( Théroux-Rancourt et al, 2020 ). However, our study demonstrated that especially when several tissues with (almost) the same gray level are located close to each other, a in-depth biological knowledge and a considerable amount of time are required for a precise segmentation (or, in the best case, to verify the correctness of the segmentation after automated segmentation).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the binary image derived from both reconstruction methods, along with the tissue boundaries, resulted in a composite image stack where each leaf tissue was classified. Leaf segmentation, which allowed us to automatically delimit different tissues across the full stack using a limited set of hand‐segmented composite slices was done using random‐forest classification (Théroux‐Rancourt et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%